Aplikasi Pengoptimalan Rute Pengiriman Barang pada PT.XYZ - Fandy Ong; Alexander Setiawan; Nova Sepadyati (Jurnal Infra, 2021)
The target company is a company engaged in the distribution of goods located in the city of Manado. Problems often faced by PT. XYZ, namely because of the large number of delivery destinations which resulted in the difficulty of arranging an effective travel sequence to distribute goods to customers according to the vehicle capacity and time desired by the customer. Therefore an information system is needed that is able to provide recommendations for a more effective delivery order based on each vehicle in the company. The system is implemented on website by using Django framework and MySQL Database. The process carried out by the system is by considering the constraints that the company has, namely in the form of maximum vehicle volume and office working hours, the system will provide recommendations for the order of delivery obtained through Google OR-Tools. The Genetic Algorithm method is also used as an alternative for later comparison. The end result of this program is a system that is able to answer the company's needs by providing recommendations for the order of delivery and information on detailed delivery for each vehicle. The test results obtained, namely Google OR-Tools got 17.04% better total distance results and 19.14% better total travel time results compared to the Genetic Algorithm method. Google OR-Tools also had 41.53% better total distance results and 41.46% better total trip time results than the company's current system. Meanwhile, the Genetic Algorithm method results in a total distance of 14.56% worse and a total trip time of 16.06% worse than Google OR-Tools. And when compared to the current company system, the Genetic Algorithm gets a total distance of 20.93% better and the total trip time result is 18.73% better than the current company system.